2021
DOI: 10.1177/1075547020987555
|View full text |Cite
|
Sign up to set email alerts
|

Fish Tales: How Narrative Modality, Emotion, and Transportation Influence Support for Sustainable Aquaculture

Abstract: Considerable research suggests narrative persuasion’s attitudinal and behavioral effects in health and environmental contexts. Whether the format of narrative presentation influences these effects, however, remains unclear. We use an online experiment ( N = 2,225), comparing text and video conditions, to evaluate how exposure to narrative influences transportation, emotions, and risk-benefit perceptions and, in turn, how such perceptions affect attitudes and behavioral intentions toward sustainable aquaculture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Thus, messages may need to grapple with these granularities about trust and benefit‐risk at the local level, rather than emphasize generic (e.g., RAS‐generic) values, benefits, and risks. Message format (e.g., narrative versus didactic content; print versus audiovisual) may also influence perceived benefits and support for aquaculture broadly (Rickard et al., 2021; Yang et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, messages may need to grapple with these granularities about trust and benefit‐risk at the local level, rather than emphasize generic (e.g., RAS‐generic) values, benefits, and risks. Message format (e.g., narrative versus didactic content; print versus audiovisual) may also influence perceived benefits and support for aquaculture broadly (Rickard et al., 2021; Yang et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they may be more receptive to the educational content embedded in the narrative with reduced counterarguing (Moyer‐Gusé, 2008). Narrative persuasion has been widely utilized in health communication research (Kreuter et al., 2007; Shen et al., 2015), and it has begun to gain traction in other risk contexts, such as environmental communication (Cooper & Nisbet, 2016; Moyer‐Gusé et al., 2019; Rickard et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the impact of conservation films on topics other than climate change is limited. Viewers of films about water conservation (Kantola et al, 1983), eco-friendly home renovations (Rhodes et al, 2016), and aquaculture (Rickard et al, 2021) generally were shown to display greater interest in environmental issues and behaviors compared with people who had not viewed these films. Environmental films about potential human risks associated with hydrofracturing and genetically modified organisms increased support for regulatory policies among viewers (Cooper & Nisbet, 2016) and contributed to greater online discourse about the environment and increased political activism (Vasi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Transportation into film has been shown to predict shifts in knowledge, attitudes, and behavior toward public health initiatives (Moyer-Gusé & Nabi, 2010; Williams et al, 2010), regulatory environmental policy (Cooper & Nisbet, 2016), aquaculture (Rickard et al, 2021), and avian conservation (Chen & Lin, 2014). Transportation usually is assessed with Green and Brock’s (2000) original scale, which measures transportation as a function of emotional involvement, cognitive attention, feelings of suspense, lack of awareness of surroundings, and mental imagery.…”
Section: Introductionmentioning
confidence: 99%